Tramp for the lord eaudiobook - Buckingham, Jamie (christianaudio, 2010)
Hiding Jewish refugees during WWII landed Corrie ten Boom in a German concentration camp. Released after ten months, she tramped the world with a burning desire to tell others that Jesus is a reality, that He lives, that He is victor. Join Corrie on a world-wide trip that could only have been planned by God.